2011
DOI: 10.5301/hip.2011.8843
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Delaminated Acetabular Articular Cartilage Using Fibrin Adhesive. Results at One to Three Years

Abstract: We describe one- to three-year results of a novel use of fibrin glue in the treatment of cartilage damage by arthroscopy in the hip. This technique uses the microfracture technique and fibrin adhesive to bond delaminated articular cartilage to the underlying subchondral bone. This is generally performed in conjunction with treatment of underlying pathology such as femoroacetabular impingement. Patients were assessed using the modified Harris Hip Score (MHHS) pre- and post-operatively, and statistical significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 29 publications
1
62
0
1
Order By: Relevance
“…The work by Stafford and colleagues 16 has demonstrated promising results with flap refixation at midterm follow-up. Conducting longer term repair outcome studies and developing tools to better identify these patients may allow the clinician to further prevent progression of hip osteoarthritis in this select population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work by Stafford and colleagues 16 has demonstrated promising results with flap refixation at midterm follow-up. Conducting longer term repair outcome studies and developing tools to better identify these patients may allow the clinician to further prevent progression of hip osteoarthritis in this select population.…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature suggests that refixation of the cartilage flap with a fibrin adhesive could provide the most favourable result in regards to joint preservation. 16 Harris hip scores for pain and function were found to be significantly better at midterm follow up. Our results provide more evidence that refixation could indeed be reasonable to consider when flaps are encountered in surgery, although further viability assays are needed.…”
Section: Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Mean mHHS was improved significantly after surgery, and in all five patients who underwent revision arthroscopy at a later date, the chondral repair appeared intact. Stafford et al [50] reported the results of 43 patients with FAI who have undergone fibrin adhesive technique for reattachment of delaminated chondral flaps. Both mHHS for pain and function improved significantly after the operation.…”
Section: Fibrin Adhesivementioning
confidence: 99%
“…6 The use of bioadhesives has been reported for the treatment of delaminating articular cartilage lesions in the hip. 7 Tzaveas and Villar 8 reported injecting fibrin adhesive into the cartilage pocket through a needle; the delaminated chondral surface was firmly pressed against bone with an angled arthroscopic punch. The fibrin adhesive set and re-bonded the delaminated chondral surface to the underlying subchondral bone.…”
mentioning
confidence: 99%